2021
DOI: 10.3390/educsci11100641
|View full text |Cite
|
Sign up to set email alerts
|

Soft Skills for Entry-Level Engineers: What Employers Want

Abstract: Among the requirements for engineering programs, the Accreditation Board of Engineering and Technology (ABET) criteria for student outcomes require students to have the ability to communicate effectively with a range of audiences, recognize ethical and professional responsibilities, function effectively on a team, and apply new knowledge. A review of literature for skills comprised within these ABET criteria determined 26 topics necessary for the entry-level and continued success of engineers. Nearly 500 compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 36 publications
3
50
1
5
Order By: Relevance
“…One way to develop learning in the classroom, teachers must be able and willing to develop a competence-based curriculum (Herianto, 2016). The benefits of measuring competence are being skilled in communication, proficient in analyzing, confident, able to compete, and able to do (Hirudayaraj et al, 2021;Ichsan et al, 2020;Nair & Fahimirad, 2019).…”
Section: Figure 2 Research Variablesmentioning
confidence: 99%
“…One way to develop learning in the classroom, teachers must be able and willing to develop a competence-based curriculum (Herianto, 2016). The benefits of measuring competence are being skilled in communication, proficient in analyzing, confident, able to compete, and able to do (Hirudayaraj et al, 2021;Ichsan et al, 2020;Nair & Fahimirad, 2019).…”
Section: Figure 2 Research Variablesmentioning
confidence: 99%
“…Recently, educational researchers and employers have placed increasing attention on the importance of soft-skills (Yusoff et al, 2012;Williams, 2015;de Villiers Scheepers et al, 2018;Teng et al, 2019;de Campos et al, 2020;Pitan & Muller, 2020;Hirudayaraj et al, 2021;Sarker et al, 2021).…”
Section: Soft Skillsmentioning
confidence: 99%
“…In summary, the literature review indicates that researchers have identified soft skills as an important factor influencing EM (Finch et al, 2012;Lievens & Sackett, 2012;Nickson et al, 2012;Yusoff et al, 2012;de Villiers Scheepers et al, 2018;Teng et al, 2019;de Campos et al, 2020;Hirudayaraj et al, 2021;Sarker et al, 2021;Wan Muda et al, 2021).…”
Section: Soft Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Problem-solving (PS) is one of the skills that should be at the forefront of STEM undergraduate education to equip our next generation of students with the tools they need to tackle the unfamiliar real-world problems facing them. PS skills are beneficial to STEM learners' success in academic and workplace environments [1]. However, there is often a disconnect between the skills that are intended to be developed and those that are actually achieved throughout a student's undergraduate program [2].…”
Section: Introductionmentioning
confidence: 99%